The impact of local and national economic conditions on legislative election results - Veiga, Francisco José (2006)
Using data for 278 Portuguese mainland municipalities, we estimate the impact of national and local economic conditions on legislative electoral outcomes over the period from the reestablishment of democracy in 1974 to the present. Empirical results indicate that the performance of the national economy is important but that the municipal situation also conditions electoral outcomes.